The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1002/etc.5620161010
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Formation of volatile mercury in high Arctic lakes

Abstract: Abstract-Formation rates of dissolved gaseous mercury (DGM) were measured in three high (74ЊN) Arctic lakes and one wetland. The rate of formation of DGM was controlled by (1) the intensity of solar radiation, particularly ultraviolet-B (280-320 nm) and ultraviolet-A (320-400 nm) wavebands and (2) the concentration of available photoreducible Hg(II) complexes. Additions of hydrogen peroxide and of fulvic acids did not enhance DGM formation rates in our experiments. This study illustrates that photoreduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 40 publications
10
47
0
Order By: Relevance
“…[52][53][54] Arctic lakes generally contain supersaturated surface water concentrations of DGM. [55,56] The latter studies reported average DGM concentrations of the order of 200 fM (40 pg L À1 ), representing ,3 % of the total dissolved Hg in lake waters. In Arctic Alaskan lakes, the DGM evasion flux was similar to the atmospheric input of Hg in summer precipitation [56] but dry deposition of Hg species was not included in this budget.…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 98%
See 1 more Smart Citation
“…[52][53][54] Arctic lakes generally contain supersaturated surface water concentrations of DGM. [55,56] The latter studies reported average DGM concentrations of the order of 200 fM (40 pg L À1 ), representing ,3 % of the total dissolved Hg in lake waters. In Arctic Alaskan lakes, the DGM evasion flux was similar to the atmospheric input of Hg in summer precipitation [56] but dry deposition of Hg species was not included in this budget.…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 98%
“…The rate is controlled by: the intensity of solar radiation, particularly the UV-B (280-320 nm) and UV-A (320-400 nm) wavebands, and the concentration of available photo-reducible Hg II complexes. [55] A model for Hg 0 with depth in the water column incorporating photoreduction, photooxidation, bioreduction and biooxidation was recently developed. [60] The model results suggest that because of: (i) light energy attenuation with depth and (ii) the presence of chloride, biologically mediated processes are likely to dominate the production of Hg 0 .…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 99%
“…Photochemically induced Hg II reduction is the predominant pathway of DGM formation in surface water (Amyot et al, 1994(Amyot et al, , 1997aCosta and Liss, 1999;Lalonde et al, 2001;Feng et al, 2004). Zhang (2006) summarized the Hg photochemical redox chemical process.…”
Section: Air-water Hg Exchangementioning
confidence: 99%
“…During such incubations, some samples are wrapped in various light filters, or kept in the dark, in order to isolate the effect of different wavebands (UV-A, UV-B, visible). Samples are occasionally spiked with reactive oxy-gen species (Amyot et al, 1997), dissolved organic carbon (Amyot et al, 1997); humic acids (Costa and Liss, 2000) or other compounds potentially involved in photoreduction reactions such as Fe(III) (Zhang and Lindberg, 2001). Photoreduction and photooxidation are known to occur simultaneously.…”
Section: Photoreduction and Photooxidation In Fresh And Sea Watermentioning
confidence: 99%